Step 1) Solve the first equation for yy:
-x + 2y = 6−x+2y=6
-x + color(red)(x) + 2y = 6 + color(red)(x)−x+x+2y=6+x
0 + 2y = 6 - x0+2y=6−x
2y = 6 - x2y=6−x
(2y)/color(red)(2) = (6 - x)/color(red)(2)2y2=6−x2
(color(red)(cancel(color(black)(2)))y)/cancel(color(red)(2)) = 6/2 - x/2
y = 3 - x/2
Step 2) Substitute 3 - x/2 for y in the second equation and solve for x:
6(3 - x/2) = x + 18
18 - (6x)/2 = x + 18
18 - 3x = x + 18
18 - 3x + color(red)(3x) - color(blue)(18) = x + 18 + color(red)(3x) - color(blue)(18)
18 - color(blue)(18) - 3x + color(red)(3x) = x + color(red)(3x) + 18 - color(blue)(18)
0 - 0 = 4x + 0
0 = 4x
0/color(red)(4) = (4x)/color(red)(4)
0 = (color(red)(cancel(color(black)(4)))x)/cancel(color(red)(4))
0 = x
x = 0